2009
DOI: 10.1063/1.3259413
|View full text |Cite
|
Sign up to set email alerts
|

Zinc and oxygen vacancies in ZnO nanorods

Abstract: Nominally undoped ZnO nanorods, which have been grown with intentionally incorporated large concentrations of zinc and oxygen vacancies, are studied with electron microscopy and photoluminescence spectroscopy at low temperature. Detailed photoluminescence studies reveal that the concentration of these defects depends on the growth conditions of the nanorods as well as on their annealing history. The optical signatures of these two defects at photoluminescence experiments are related with the 3.31 and 3.235 eV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 35 publications
5
15
0
Order By: Relevance
“…51 This value is in good agreement with the binding energy of 123 meV above the valence-band maximum calculated for the V 0 Zn in ZnO. 52 Further argument in favor of the attribution of the 3.33 eV emission to the BEs on V 0…”
Section: Implications Of the Experimental Resultssupporting
confidence: 73%
“…51 This value is in good agreement with the binding energy of 123 meV above the valence-band maximum calculated for the V 0 Zn in ZnO. 52 Further argument in favor of the attribution of the 3.33 eV emission to the BEs on V 0…”
Section: Implications Of the Experimental Resultssupporting
confidence: 73%
“…1 that the intensity of the peak D, at 3.359 eV, which corresponds to the ABX, follows the change of the intensity of the V Zn peak, while that of the DBX at 3.364 eV follows the Zn i related peak. This behavior, on one hand, confirms our previous [10] assignment of ABX as bound excitons to the zinc vacancy defects, while on the other, shows that the peak DBX is due to the excitons bound to the Zn i related defects which are donors.…”
Section: Methodssupporting
confidence: 89%
“…In a previous work [10], we have shown that the 3.308 eV peak is related to a free to acceptor transition with the acceptor being the zinc vacancy, V Zn , with E a ¼ 123 meV, while the optical signature of the corresponding bound exciton, ABX, is the peak at 3.359 eV. Less intense peaks and shoulders, below 3.308 eV, are phonon replicas of the above main peaks, assuming that the LO phonon of ZnO is 72 meV [13].…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations